Adaptive regulations of Nrf2 alleviates silver nanoparticles-induced oxidative stress-related liver cells injury. (5th January 2023) - Guo, Menghao; Zhang, Wenli; Niu, Shuyan; Shang, Mengting; Chang, Xiaoru; Wu, Tianshu; Zhang, Ting; Tang, Meng; Xue, Yuying
Abstract: Silver nanoparticles (AgNPs) are widely used in various fields such as industry, agriculture, and medical care because of their excellent broad-spectrum antibacterial activity. However, their extensive use has raised concerns about their health risks. Liver is one of the main target organs for the accumulation and action of AgNPs. Therefore, evaluating the toxic effects of AgNPs on liver cells and its mechanisms of action is crucial for the safe application of AgNPs. In the study, polyvinylpyrrolidone (PVP)-coated AgNPs were characterized. The human hepatoma cell line (HepG2) and the normal hepatic cell line (L02) were exposed to different concentrations of AgNPs (20–160 μg/mL) and pretreated with the addition of N -acetylcysteine (NAC) or by Nrf2 siRNA transfection. NAC was able to inhibit the concentration-dependent increase in the level of apoptosis induced by AgNPs in HepG2 cells and L02 cells. Interestingly, HepG2 cells were more sensitive to AgNPs than L02 cells, and this may be related to the different ROS generation and responses to AgNPs by cancer cells and normal cells. In addition, NAC also alleviated the imbalance of antioxidant system and cell cycle arrest, which may be related to AgNPs-induced DNA damage and autophagy. The knockdown of nuclear factor erythroid-derived factor 2-related factor (Nrf2) found that AgNPs-induced ROS and apoptosis levels were further upregulated, but the cell cycle arrest was alleviated. On the whole, Nrf2 exerts a protective role in AgNPs-induced hepatotoxicity. This study complements the hepatotoxicity mechanisms of AgNPs and provides data for a future exploration of AgNPs-related anti-hepatocellular carcinoma drugs. Graphical abstract: Image 1 Highlights: AgNPs induced a concentration-dependent decline in HepG2 and L02 cells viability. AgNPs induced ROS increase and apoptosis in HepG2 and L02 cells. AgNPs induced DNA damage, autophagy and cell cycle arrest in HepG2 and L02 cells. N -acetylcysteine alleviated AgNPs-induced cytotoxicity in HepG2 and L02 cells. Nrf2 siRNA aggravated AgNPs-induced cytotoxicity in HepG2 and L02 cells.